SMALL SCALE PILOT PLANT THERMAL DRYER FOR DOMESTIC WASTEWATER SLUDGE DRYING SYSTEM - ZAKARIA, MOHD SAFUAN (2017)
Domestic Wastewater Sludge (DWS) is considered as one of the largest contributors waste in Malaysia. Currently, the disposal method for DWS in Malaysia which is by landfilling cannot sustain the production of the DWS produced by the country. Converting this waste as an alternative fuel can eliminate the disposal problem and reduce the environmental issue that causes by this waste. The initial moisture content in DWS is around 90% and in order to convert this waste into useful solid fuel, the moisture content of this waste must be reduced to 20% and below. Previous work only produced small quantity of dried DWS by using the microwave oven. This method of drying consumed high energy and not practical for real application. So far, there is less effort to develop large scale of DWS drying for conversion into fuel. Thermal dryer is one of the efficient dryer for the DWS that is capable of drying the huge volume of DWS in a short period of time. The thermal dryer for the DWS which used screw type thermal dryer were tested in several operating conditions that can meet the requirement as a potential of solid fuel. The study also is to determine the best operating condition of the thermal dryer and the characteristic of the dried sludge that is produced from the dryer. The characteristic dried DWS that is produced from the thermal dryer were analyzed in determining the moisture content and heating value. The higher heating value of the DWS recorded by this study was slightly lower since some of the volatile matter in the DWS was diminished during the drying process due to the high operating temperature of more than 100°C. The result shows that the moisture content of the DWS decreased with increasing power rating of the burner in the thermal dryer. There were 70 operating conditions that produced dried DWS with less than 20% by weight of the moisture content. However, the operating condition that consumed less energy was preferable. After analysis and comparison of the energy gained and energy consumed by the dryer, the best operating condition of the thermal dryer was at 275 kW of power rating with speed of 30 and 10 rpm (revolution per minute) of the screw conveyor in the feeder and dryer respectively.